2023
DOI: 10.1101/2023.09.28.560070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Curcumin and turmeric extract inhibit SARS-CoV-2 pseudovirus cell entry and spike-mediated cell fusion

Endah Puji Septisetyani,
Dinda Lestari,
Komang Alit Paramitasari
et al.

Abstract: Turmeric extract (TE) with curcumin as its main active ingredient has been studied as a potential COVID-19 therapeutic. Curcumin has been studied in silico and in vitro against a naive SARS-CoV-2 virus, yet little is known about TE’s impact on SARS-CoV-2 infection. Moreover, no study reveals the potentials of both curcumin and TE on the inhibition of SARS-CoV-2 cell-to-cell transmission. Here, we investigated the effects of both curcumin and TE on the inhibition of SARS-CoV-2 entry and cell-to-cell transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Studies reveal that phytochemicals can effectively target and disrupt the S-protein-mediated membrane fusion. For instance, curcumin, a diarylheptanoid from Curcuma longa , was found to impede SARS-CoV-2 entry in 293T/hACE/TMPRSS2 cells by blocking pseudovirus entry [ 10 ]. Similarly, emodin, an anthraquinone from Rheum officinale , significantly reduces the interaction between the S-protein and ACE2 [ 11 ] Moreover, our research, in conjunction with others, has identified a link between the chemical structure of oleanane-type saponins and their effectiveness as inhibitors of membrane fusion affected by SARS-CoV-2 [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies reveal that phytochemicals can effectively target and disrupt the S-protein-mediated membrane fusion. For instance, curcumin, a diarylheptanoid from Curcuma longa , was found to impede SARS-CoV-2 entry in 293T/hACE/TMPRSS2 cells by blocking pseudovirus entry [ 10 ]. Similarly, emodin, an anthraquinone from Rheum officinale , significantly reduces the interaction between the S-protein and ACE2 [ 11 ] Moreover, our research, in conjunction with others, has identified a link between the chemical structure of oleanane-type saponins and their effectiveness as inhibitors of membrane fusion affected by SARS-CoV-2 [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%